The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1468-036x.2008.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Interest Rate Risk Rewards in Stock Returns of Financial Corporations: Evidence from Germany

Abstract: The interest rate sensitivity of stock returns of financial and non-financial corporations is a well-known phenomenon. However, only little is known about the part of total stock returns that is attributable to the compensation an investor receives for being exposed to interest rate risk when investing in equity securities. We pursue here a benchmark portfolio approach, constructing benchmark portfolios having the same interest rate risk exposure as a particular stock. By studying the time series of returns of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 56 publications
(107 reference statements)
1
25
0
Order By: Relevance
“…This approach was pioneered by Stone (1974) and has recently been applied by several authors to European financial corporations, including Oertmann et al . (2000) and Czaja et al . (2009a, 2009b).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…This approach was pioneered by Stone (1974) and has recently been applied by several authors to European financial corporations, including Oertmann et al . (2000) and Czaja et al . (2009a, 2009b).…”
mentioning
confidence: 95%
“…7 There are also numerous models and papers that analyse the interest rate sensitivity of (exchange-traded) banks based on stock returns rather than on accounting-based regulatory data. This approach was pioneered byStone (1974) and has recently been applied by several authors to European financial corporations, includingOertmann et al (2000) andCzaja et al (2009aCzaja et al ( , 2009b. However, because in many countries (including Germany) most banks are not listed, this approach to analysing the interest rate risk is not universally applicable for supervisory purposes.…”
mentioning
confidence: 99%
“…Adjustment of all benchmark rates can affect a stock price. For example, the investment value of a security may decrease during an increasing period, bringing about stock price dropping; in the contrary situation, the result shows an opposite direction [8]. Numerous empirical studies exist on the potential influence of inflation/level of GDP on the evolution of the assets' price (see Weale and Wieladek [9] for a recent analysis of these aspects).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study confirmed that stock returns are partially predictable while rejecting the random walk model. In another study, Czaja and Scholz (2009) examined the sensitivity of German stock returns to interest rate changes and concluded that the industry curvature and, to a lesser extent, the slope of the term structure, are useful in predicting variations in stock returns. The study also found that interest rate risk was of greater relevance for financial institutions than non-financial institutions.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%